2017
DOI: 10.1016/j.pjnns.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of language centers in patients with brain tumors located in eloquent speech areas – A pre- and postoperative preliminary fMRI study

Abstract: In the cases of tumors localized near the left Broca's area, a transfer of the function to the healthy hemisphere seems to take place. Resection of tumors located near Broca's or Wernicke's areas may lead to relocation of the brain language centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…The total number of patients that were studied was 170. The sample size ranged from 10 [52] to 42 participants [50]. Patients' mean age ranged from 30.9 ± 7.4 years [50] to 53.1 ± 13.1 years [46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of patients that were studied was 170. The sample size ranged from 10 [52] to 42 participants [50]. Patients' mean age ranged from 30.9 ± 7.4 years [50] to 53.1 ± 13.1 years [46].…”
Section: Resultsmentioning
confidence: 99%
“…Tumor size was specified in five studies (5/8) [45, 46, 5052], one reported only resected volume [47]. The extent of resection was included in six investigations (6/8) [45, 46, 4851].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, inter-hemispheric activations in the homologous language areas were evidenced, with an activation of the right “Broca’s area” in five frontal LGG patients without language disorders, and with an activation of the right “Wernicke’s area” in five temporal gliomas, both before and after surgery [ 113 ]. In a patient with resection for a left LGG near the “Broca’s area”, without language impairment, fMRI achieved before surgery and 3, 32, and 41 months after resection demonstrated a progressive right-sided activation of Broca’s and Wernicke’s areas [ 114 ].…”
Section: Functional Compensation After Lgg Surgery: Postoperative mentioning
confidence: 99%
“…Concerning language, reorganization in the affected hemisphere was observed for left Wernicke’s area (e.g., Gębska-Kośla et al, 2017 ) and the left mesial temporal cortex (e.g., Kamada et al, 2004 ). Gębska-Kośla et al (2017) observed that tumor resection in either Broca’s or Wernicke’s area restored the primary activation of the ipsilesional ( vs . contralesional) hemisphere in some of the patients (the others presented with unchanged patterns).…”
Section: Postoperative Plasticitymentioning
confidence: 99%